Perilaku siswa SDN 4 Antiga Kelod Karangasem terhadap infeksi soil transmitted helminth - Ketut Teddy Bayu Pradinata; I Made Sudarmaja; Ni Luh Ariwati (Intisari Sains Medis, 2019)
Introduction: Soil Transmitted Helminths or (STH) is a group of parasitic worms (class of Nematodes) that can cause infection in humans through contact with the parasitic eggs or larvae themselves that develop in moist soils found in tropical countries and subtropics. Factors that can cause STH infection are due to lack of hygiene. This study aims to determine The correlation of Student’s behavior at SDN 4 Antiga Kelod, Karangasem and the Infection of Soil Transmitted HelminthMethod: This is a cross-sectional study. The source of the data came from primary data. Distribution of research variables are hand washing habits, nail cutting habits, open defecation habits, and behavior not using footwear. Data analysis is described in the form of tables and narratives.Result: From total 125 samples, 46 who had STH infection (33.09%), rare / never washed hands who had infections received a percentage of 100%, samples did not wear footwear infected with 74.4% with an OR of 14, an unclean nail sample infected at 86.5% with an OR of 34, a sample of the Chapter not in place that was infected was 52.6% with an OR of 2.Conclusion: The behavior of not using footwear properly has a 14 times greater risk than children who use footwear well to be infected with helminthiasis. unclean nail behavior has a risk 34 times greater than children who have clean nails to be infected with helminthiasis. Defecation behavior does not have the risk of being twice as large as in children who are defecating in the toilet to be infected with helminthiasis.Latar Belakang: Soil Transmitted Helminths atau (STH) adalah sekelompok cacing parasit (kelas Nematoda) yang dapat menyebabkan infeksi pada manusia melalui kontak dengan telur ataupun larva parasit itu sendiri yang berkembang di tanah yang lembab yang terdapat di negara yang beriklim tropis maupun subtropics. Faktor-faktor yang dapat menyebabkan terinfeksi STH yaitu oleh karena kurangnya perilaku menjaga kebersihan. penelitian ini bertujuan untuk mengetahui perilaku Siswa SDN 4 Antiga Kelod Karangasem Terhadap Infeksi Soil Transmitted Helminth.Metode: Penelitian ini merupakan suatu penelitian cross-sectional. Sumber data berasal dari data primer. Distribusi variabel penelitian yaitu Kebiasaan mencuci tangan, Kebiasaan memotong kuku, kebiasaan buang air besar sembarangan, dan perilaku tidak menggunakan alas kaki. Analisis data di paparkan dalam bentuk tabel dan narasi.Hasil: dari 125 sampel, yang mengalami infeksi STH sebanyak 46 sampel (33,09%), sampel jarang/tidak pernah cuci tangan yang mengalami infeksi mendapatkan persentase sebesar 100%, sampel tidak memakai alas kaki yang terinfeksi sebesar 74,4% dengan OR sebesar 14, sampel kuku tidak bersih yang terinfeksi sebesar 86,5% denga OR sebesar 34, sampel Bab tidak pada jamban yang terinfeksi sebesar 52,6% dengan OR sebesar 2.Simpulan: Perilaku tidak menggunakan alas kaki dengan baik memiliki resiko 14 kali lebih besar sibanding anak yang menggunakan alas kaki dengan baik untuk terinfeksi penyakit kecacingan. Perilaku kuku tidak bersih memiliki resiko 34 kali lebih besar dibanding anak yang memiliki kuku bersih untuk terinfeksi penyakit kecacingan. Perilaku BAB tidak pada tempatya memiliki resiko 2 kali lebih besar dibanding anak yang BAB pada jamban untuk terinfeksi penyakit kecacingan.